Response and conflict expectations shape motor responses interactively - Annika E. Sauter; Adam Zabicki; Thomas Schüller; Juan Carlos Baldermann; Gereon R. Fink; Paola Mengotti; Simone Vossel (Experimental Brain Research, 2024)
Efficient responses in dynamic environments rely on a combination of readiness and flexibility, regulated by anticipatory and online response control mechanisms. The latter are required when a motor response needs to be reprogrammed or when flanker stimuli induce response conflict and they are crucially modulated by anticipatory signals such as response and conflict expectations. The mutual influence and interplay of these control processes remain to be elucidated. Our behavioral study employed a novel combined response cueing/conflict task designed to test for interactive effects of response reprogramming and conflict resolution and their modulation by expectations. To this end, valid and invalid response cues were combined with congruent and incongruent target flankers. Expectations were modulated by systematically manipulating the proportions of valid versus invalid cues and congruent versus incongruent flanker stimuli in different task blocks. Reaction time and accuracy were assessed in thirty-one healthy volunteers. The results revealed response reprogramming and conflict resolution interactions for both behavioral measures, modulated by response and conflict expectations. Accuracy decreased disproportionally when invalidly cued targets with incongruent flankers were least expected. These findings support coordinated and partially overlapping anticipatory and online response control mechanisms within motor-cognitive networks.

Combined expectancies: the role of expectations for the coding of salient bottom-up signals - Michael Wiesing; Gereon R. Fink; Ralph Weidner; Simone Vossel (Experimental Brain Research, 2020)
The visual system forms predictions about upcoming visual features based on previous visual experiences. Such predictions impact on current perception, so that expected stimuli can be detected faster and with higher accuracy. A key question is how these predictions are formed and on which levels of processing they arise. Particularly, predictions could be formed on early levels of processing, where visual features are represented separately, or might require higher levels of processing, with predictions formed based on full object representations that involve combinations of visual features. In four experiments, the present study investigated whether the visual system forms joint prediction errors or whether expectations about different visual features such as color and orientation are formed independently. The first experiment revealed that task-irrelevant and implicitly learned expectations were formed independently when the features were separately bound to different objects. In a second experiment, no evidence for a mutual influence of both types of task-irrelevant and implicitly formed feature expectations was observed, although both visual features were assigned to the same objects. A third experiment confirmed the findings of the previous experiments for explicitly rather than implicitly formed expectations. Finally, no evidence for a mutual influence of different feature expectations was observed when features were assigned to a single centrally presented object. Overall, the present results do not support the view that object feature binding generates joint feature-based expectancies of different object features. Rather, the results suggest that expectations for color and orientation are processed and resolved independently at the feature level.

The impact of probabilistic feature cueing depends on the level of cue abstraction - Pascasie L. Dombert; Gereon R. Fink; Simone Vossel (Experimental Brain Research, 2016)

Direction and magnitude of nicotine effects on the fMRI BOLD response are related to nicotine effects on behavioral performance - Tracy Warbrick; Arian Mobascher; Juergen Brinkmeyer; Francesco Musso; Tony Stoecker; N. Jon Shah; Simone Vossel; Georg Winterer (Psychopharmacology, 2011)